(untitled) (Global Journal of Management and Business Research, 2016)
The MSME sector is considered to be the engine of growth for an economy. The estimated contribution of Micro, Small and Medium Enterprises (MSME) sector, including service segment, to the country#x2019;s GDP during 2012-13 was 37.54 per cent; while the total employment in the sector is 805.24 Lakh. The contribution of the sector to India#x2019;s total export for the year 2014- 15 was 44.70 per cent. Also the problems of poverty and inequality are deep- rooted, especially in developing countries like India. To address these problems, we need a system of #x2018;Inclusive Growth#x2019;. Growth cannot be inclusive unless and until the fruits of the growth is percolated to the bottom of pyramid. Specifically in a developing nation like India where inequality in distribution of wealth and income is significantly high, sustained increase in per capita income cannot be translated automatically to sustained increase in standard of living.